2008
DOI: 10.1002/app.27934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon fillers on the thermal conductivity of highly filled liquid‐crystal polymer based resins

Abstract: The thermal conductivity of insulating polymers can be increased by the addition of conductive fillers. One potential market for these thermally conductive resins is for fuel cell bipolar plates. In this study, various amounts of three different carbon fillers (carbon black, synthetic graphite particles, and carbon fiber) were added to Vectra A950RX liquid crystal polymer. Because the resulting composites were anisotropic, they were tested for both through-plane and in-plane thermal conductivities. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Typical thermal conductivity values of some common thermoplastics are usually between 0.1 and 0.4 W/mK . To improve the thermal conductivity of a polymeric material, polymer matrices are usually filled with thermally conductive fillers such as metal powders , ceramic powders , and carbon‐based materials .…”
Section: Introductionmentioning
confidence: 99%
“…Typical thermal conductivity values of some common thermoplastics are usually between 0.1 and 0.4 W/mK . To improve the thermal conductivity of a polymeric material, polymer matrices are usually filled with thermally conductive fillers such as metal powders , ceramic powders , and carbon‐based materials .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the use of a mixture of filler materials increases thermal conductivity of polymer/filler composites. 15,19,20 Therefore, in this study, the effect of graphite/carbon fiber, graphite/MWCNT, and carbon fiber/MWCNT mixtures on parallel thermal conductivity of the oriented composites is investigated as shown in Figure 10. Total content of fillers in Figure 10 is fixed at 10%.…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16] However, its poor thermal conductivity (0.014 W m À1 K À1 ) is a major disadvantage that hinders the widespread applications of PVC. 17,18 If a PVC-based material is modied by lling with thermally conductive agents that replace the expensive metals, it would concomitantly enhance the cost effectiveness and broaden the spectrum of applications for PVC to areas like heat transfer, electronic packaging, and architectural coverings. 2 Traditional methods for improving the thermal properties of conductive polymer composites include in situ polymerization, 19 solution blending 20 and melt-mixing.…”
Section: Introductionmentioning
confidence: 99%